(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
This study examined the nexus between total quality management (continuous improvement, teamwork) and employee engagement within construction firms in Port Harcourt, Nigeria. The study was a correlational research design, data was collected from 249 employees of selected construction companies and analyzed using Pearson’s correlation coefficient. The findings reveal that continuous improvement has a moderate impact on employee engagement, indicating that process optimization alone is insufficient to drive workforce commitment. However, teamwork demonstrates a significantly stronger correlation with engagement, highlighting the importance of collaborative work environments in enhancing productivity and project success. The study underscores the need for construction firms to integrate structured continuous improvement initiatives such as Lean Construction and Six Sigma methodologies while fostering a culture of teamwork through cross-functional collaboration and incentive-driven performance systems. Additionally, leadership commitment is crucial in embedding quality management practices into organizational strategy.